Strategi Pembelajaran Berbasis Kontekstual dalam Mengaitkan Materi dengan Kehidupan Sehari-hari - Rizki Amelia Siregar; Nuraida, Nuraida; Gusmaneli, Gusmaneli (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effectiveness of contextual-based learning strategies in linking instructional materials to students’ daily lives. The contextual approach (Contextual Teaching and Learning) emphasizes students’ active involvement in constructing knowledge through real-life experiences, thereby fostering meaningful learning. This research employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that the implementation of contextual-based learning strategies significantly enhances students’ conceptual understanding, strengthens critical thinking skills, and increases learning motivation. Learning becomes more relevant and applicable as the materials are directly connected to students’ real-life contexts, including family, school, and community environments. The implementation of this strategy involves various methods, such as problem-based learning, group discussions, and the use of real-life case studies. However, several challenges were identified, including time constraints, teachers’ readiness, and differences in students’ characteristics. In conclusion, contextual-based learning strategies are effective in creating meaningful and relevant learning experiences connected to students’ daily lives. Therefore, strengthening teachers’ pedagogical competence and providing supportive educational environments are essential to optimize the implementation of this approach.